Unexpected BrdU inhibition on astrocyte-to-neuron conversion - Tao Wang; Jian-Cheng Liao; Xu Wang; Qing-Song Wang; Kai-Ying Wan; Yi-Yi Yang; Qing He; Jia-Xuan Zhang; Gong Chen; Wen Li (Neural Regeneration Research, 2022)
5-Bromo-2′-deoxyuridine (BrdU) is a halogenated pyrimidine that can be incorporated into newly synthesized DNA during the S phase of the cell cycle. BrdU is widely used in fate-mapping studies of embryonic and adult neurogenesis to identify newborn neurons, however side effects on neural stem cells and their progeny have been reported. In vivo astrocyte-to-neuron (AtN) conversion is a new approach for generating newborn neurons by directly converting endogenous astrocytes into neurons. The BrdU-labeling strategy has been used to trace astrocyte-converted neurons, but whether BrdU has any effect on the AtN conversion is unknown. Here, while conducting a NeuroD1-mediated AtN conversion study using BrdU to label dividing reactive astrocytes following ischemic injury, we accidentally discovered that BrdU inhibited AtN conversion. We initially found a gradual reduction in BrdU-labeled astrocytes during NeuroD1-mediated AtN conversion in the mouse cortex. Although most NeuroD1-infected astrocytes were converted into neurons, the number of BrdU-labeled neurons was surprisingly low. To exclude the possibility that this BrdU inhibition was caused by the ischemic injury, we conducted an in vitro AtN conversion study by overexpressing NeuroD1 in cultured cortical astrocytes in the presence or absence of BrdU. Surprisingly, we also found a significantly lower conversion rate and a smaller number of converted neurons in the BrdU-treated group compared with the untreated group. These results revealed an unexpected inhibitory effect of BrdU on AtN conversion, suggesting more caution is needed when using BrdU in AtN conversion studies and in data interpretation.